Value added statement: A relevant instrument for integrated reporting - Anna Bagieńska (e-Finanse: Financial Internet Quarterly, 2016)
The integrated report is a tool enabling communication of an enterprise with both internal and external stakeholders. The lack of unanimity of stakeholders' opinions on building values, resulting from the differentiation of their access to information, results in the value of the enterprise in the economic sense, evaluated from inside the organization, not complying with the market value evaluated by investors on the basis of available information. As a result, there is a gap of enterprise value. The lack of an integrated report leads to searching for such solutions whose scope and informational quality would build appropriate social-economic solutions with stakeholders. The report on added value is one of the ways of communication with the stakeholders in the area of the value generated by the enterprise. The purpose: The aim is to identify operating enterprises realizing the strategy of social responsibility in the ways of reporting on the information regarding added value as well as preparing the conception of a report indicating the direction of allocation of the generated added value for building financial, human and social capital of a firm.
Keywords: L21; M21; M12; 330; Value added statement; integrated reporting; CSR; intellectual capital